Suramin Exerts an Ameliorative Effect on Acetic Acid-Induced Acute Colitis in Rats by Demonstrating Potent Antioxidant and Anti-Inflammatory Properties - Gulcin Ercan; Hatice Aygün; Ahmet Akbaş; Osman Sezer Çınaroğlu; Oytun Erbas (Medicina)
Background and Objectives: The purpose of this study was to evaluate potential protective effects of suramin on inflammation, oxidative stress, and histopathological damage a rat model of acute colitis created with acetic acid. Materials and Methods: Wistar albino (male) rats were randomly assigned to three groups: control (n = 10), colitis + saline (n = 10), and colitis + suramin (n = 10). Rectal instillation of 4% acetic acid was used to induce acute colitis. Suramin (10 mg/kg/day) or saline was administered intraperitoneally for 15 days. Plasma concentrations of pentraxin 3 (PTX3), tumor necrosis factor-alpha (TNF-α), neutrophil extracellular traps (NETs), and malondialdehyde (MDA) were determined using enzyme-linked immunosorbent assay (ELISA) and spectrophotometric methods. In addition, vascular endothelial growth factor (VEGF) and TNF-α levels in colonic tissue were also measured. Histopathological evaluations were conducted using hematoxylin and eosin staining. Results: Significant increases in plasma and tissue inflammatory markers, oxidative stress parameters, and histopathological scores were observed when compared to control group; values were higher in colitis group. Suramin treatment significantly reduced plasma PTX3, TNF-α, NETs, and MDA levels, and colonic TNF-α and VEGF concentrations compared to the untreated colitis group. Histological analysis showed reduced epithelial injury and leukocyte presence in rats receiving suramin. Conclusions: Our findings demonstrate that suramin significantly attenuates inflammatory and oxidative damage in an experimental model of acute colitis. These results suggest that suramin may possess therapeutic potential in intestinal inflammation; however, this effect requires further support through advanced experimental and clinical studies.